Almsgiving as a rhetorical device in 4QTobit? - Evans, Annette H. (HTS teologiese studies, 2018)
This article is a sequel to an earlier exploration of the possibility of a shift in the Book of Tobit from the Deuteronomistic theological perspective in the beginning to a more nuanced concept of theodicy in the end. The Semitic versions of Tobit found at Qumran are regarded as the earliest witnesses to the story of Tobit, dating from ca. 100 BCE to the early part of the 1st century CE. They are very fragmentary, but the theme of almsgiving recurs at regular intervals in the narrative. In the beginning the Deuteronomistic theological perspective is expressed in terms of Tobit’s belief that God will reward with prosperity those who give alms to their own kinsmen, but towards the end the ideology appears to shift from the rather self-centred ‘prosperity cult’ orientation to a different motivation for almsgiving. The aim of this article is to test the possibility that the almsgiving references are rhetorical hinges that mark the movement of the narrative into a different ideological viewpoint. The complexity of the manuscript transmission of the story of Tobit in the larger matrix of diachronic cultural and religious trends in the ancient Near East is kept in mind when text-critical problems are encountered.